Size-Dependent Wetting Contact Angles at the Nanoscale Defined by Equimolar Surfaces and Surfaces of Tension - Sergii Burian; Yevhenii Shportun; Andriy Yaroshchuk; Leonid Bulavin; David Lacroix; Mykola Isaiev (Scientific Reports)
Abstract The wetting characteristics of fluids play a crucial role in various fields of interface and surface science. Contact angle serves as a fundamental indicator of wetting behavior. However, accurate quantification of wetting phenomena even at the macroscale often poses challenges, particularly due to the hysteresis between receding and advancing contact angles. The complexity increases further at the nanoscale, where the significant volume of the interphase region causes ambiguity in defining the “dividing surface.” In this study, we use molecular dynamics simulations to investigate the wetting dynamics of a “cylindrical nanodroplet” and an argon nanofilm. Through analysis of microscopic density distribution maps and tension tensor distributions within the Gibbs framework, we identified equimolar and tension surfaces at both liquid-gas and liquid-solid interfaces. Our results show over 10% discrepancies between equilibrium contact angles calculated for equimolar surfaces and those based on tension surfaces in the case of the cylindrical nanodroplet. We observed a clear dependence of wetting contact angles on the cross-sectional radius of cylindrical droplets with a straight three-phase contact line. As the radius decreases, the differences between contact angles at equimolar and tension surfaces increase, while for larger droplets, these differences diminish and become negligible.